Body composition reference ranges in community‐dwelling adults using dual‐energy X‐ray absorptiometry: the Australian Body Composition (ABC) Study. Issue 4 (14th May 2021) - Kirk, Ben; Bani Hassan, Ebrahim; Brennan‐Olsen, Sharon; Vogrin, Sara; Bird, Stefanie; Zanker, Jesse; Phu, Steven; Meerkin, Jarrod D.; Heymsfield, Steven B.; Duque, Gustavo
Abstract: Background: Reference ranges for lean mass (LM) and fat mass (FM) are essential in identifying soft tissue disorders; however, no such reference ranges exist for the most commonly used Hologic dual‐energy X‐ray absorptiometry (DXA) machine in Australia. Methods: Cross‐sectional study of community‐dwelling adults (aged 18–88 years) who underwent a Hologic DXA scan at one of three commercialized densitometry centres in Australia. Age‐specific and sex‐specific percentile curves were generated for LM [LM, appendicular lean mass (ALM), ALM adjusted for height squared (ALM/h 2 ), and ALM adjusted for body mass index (ALM/BMI)] and FM [FM, FM adjusted for height squared (FM/h 2 ), appendicular fat mass, and android and gynoid fat] parameters using the LMS statistical method. Cutpoints equivalent to T ‐scores of −1, −2, and −2.5 standard deviations below the young mean reference group (20–29 years) were also generated for LM parameters. Results: A total of 15 479 community‐dwelling adults (54% men) with a median age of 33 years (interquartile range: 28, 42) were included. LM, ALM, and ALM/h 2 remained stable until age 50, after which these parameters started to decline in both sexes. Compared with age 50, median percentiles of LM, ALM, and ALM/h 2 declined by −5.9 kg, −3.7 kg, and −0.86 kg/m 2 in men and by −2.5 kg, −1.8 kg, and −0.10 kg/m 2 in women at age 70, respectively. Adjusting ALM for BMI (rather than height squared) resulted in different trends, with ALM/BMI decreasing from as early as age 20. Compared with age 20, median percentiles of ALM/BMI at age 40 declined by −0.10 kg/kg/m 2 in men and by −0.06 kg/kg/m 2 in women; and at age 70, ALM/BMI declined by −0.25 kg/kg/m 2 in men and by −0.20 kg/kg/m 2 in women. Cutpoints equivalent to T ‐scores of −1, −2, and −2.5 standard deviations for ALM/BMI were 1.01, 0.86, and 0.77 kg/kg/m 2 in men and 0.70, 0.59, and 0.53 kg/kg/m 2 in women, respectively. All FM parameters progressively increased from age 20 and continued up until age 70. Conclusions: We developed reference ranges for LM and FM parameters from Hologic DXA machines in a large cohort of Australian adults, which will assist researchers and clinicians in identifying soft tissue disorders such as obesity, sarcopenia, and cachexia.